Correlating Temperature, Airtightness, and Pollutant Concentrations: Insights into Indoor Air Quality in Ajman Apartment Buildings (Future Cities and Environment, 2024)
This paper presents a comprehensive assessment of indoor air quality (IAQ) in newly constructed apartment buildings in small and medium-sized cities, with a specific focus on formaldehyde (HCHO) and volatile organic compounds (VOCs) as major contributors to sick building syndrome (SBS). The study aims to measure using the World Health Organization (WHO) process test method and compare the concentrations of HCHO and TVOC indoors and outdoors, assess the indoor temperature levels, evaluate the airtightness performance, and analyze the impact of these factors on IAQ. The research was conducted in Yasmeen Tower and Al Wahat Tower in Ajman Al Jurf area. The results showed that in Yasmeen Tower, unoccupied one-bedroom units had high concentrations of HCHO and TVOC. The average HCHO concentration was 198 μg/m3, with the highest recorded concentration at 265 μg/m3. The average TVOC concentration was 1,244 μg/m3. In Al Wahat Tower, even higher levels of HCHO were observed. The highest recorded concentration reached 445 μg/m3, with an average of 323 μg/m3. Airtightness performance was assessed, with the effective leakage area ranging from 139 cm2 to 301 cm2 for the 7 units, averaging at 193 cm2. One bedroom units exhibited higher airtightness. Correlation analysis revealed a strong relationship between room temperature and both HCHO and TVOC concentrations, indicating that higher room temperatures were associated with increased pollutant levels. Moreover, improved airtightness performance correlated with decreased HCHO and TVOC concentrations. The findings emphasize the importance of effective ventilation systems, temperature control, and airtightness measures to mitigate indoor air pollutants and enhance IAQ in multi-unit dwellings. The study provides valuable insights for policymakers, architects, and residents to address IAQ concerns and promote healthier indoor environments. However, the study’s limitations should be considered, and further research is recommended to broaden the understanding of IAQ in residential buildings.